PERBANDINGAN METODE TREND MOMENT DAN LEAST SQUARE DALAM MENYUSUN ANGGARAN PENJUALAN - Retnosari Retnosari (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
The purpose of this study was to determine sales forecasting using the trend moment method, knowing sales forecasting using least square method, knowing the comparison of sales forecasting using the trend moment and least square method at UD Mitra Sejahtera Plastindo Kebumen.The results of forecasting the sale of HDPE plastic in 2016 at UD Mitra Sejahtera Plastindo use the trend moment method for the Cilacap region, small size plastic 424.8 bal, responsibility 3,502.6 bales, large 296.7 bales, jumbo 67.74 bales, super 32.64 bal. The area of ??Banjarnegara is small size 806.28 bales, responsibility 3,853.5 bales, large 408.6 bales, jumbo 186.3 bal, super 146.6 bales. The small size of the Purwokerto area is 1,949.16 bales, the responsibility is 6,053.1 bales, large is 649.44 bales, jumbo is 205.5 bal, super is 54.06 bal.The results of forecasting the sale of HDPE plastics in 2016 at UD Mitra Sejahtera Plastindo used the least square method for the Cilacap area, a small plastic size of 390.3 bales, 3453 balances, a large 277.26 bales, jumbo 61.56 bales, super 30.3 bales. The area of ??Banjarnegara is small size 801.6 bales, responsibility 3,592.26 bales, large 379.74 bales, jumbo 157.5 bales, super 125.66 bales. The Purwokerto area is 1,904.7 bal in small size, 5994 bales in liability, 499.2 bal in bulk, 186.6 bal in jumbo, and 50.7 bal in super.The results of forecasting the sale of HDPE plastic to Plastindo Prosperous UD Partners using the moment and least square trend method shows that sales forecasting uses the trend moment method is greater than the least square method, so the forecasting results using the least square method close to the realization of sales, the difference forecasting with sales realization January is very small in the Banjarnegara region, namely, small size 1.47 bales, responsibility 1.04 bales, large 0.61 bales, jumbo 0.20 bales, super 0.08 bales.